2018
DOI: 10.5185/amlett.2018.1828
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/organoclay biodegradable nanocomposites: dissimilar tendencies of different clay modifiers

Abstract: In this work, biodegradable nanocomposites based on polycaprolactone (PCL) reinforced with 2.5, 5.0 and 7.5 wt.% of two different clays, a commercial organo-clay (Cloisite 20A, C20A) and a laboratory modified bentonite with tributylhexadecyl phosphonium bromide (bTBHP), were prepared by melt intercalation followed by compression molding. The study contemplates the analysis of chemical (Infrared Spectrometry, FTIR), morphological (X-Ray Diffractometry, XRD, Scanning Electron Microscopy, SEM, and Transmission El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The Fig. 7 Scheme of the structure of montmorillonite Nanoclays commonly used in polymer Nanocomposites are montmorillonite and bentonite [68]. They consist on two layer aluminosilicates 2:1 type, and its unit cell is formed by two silicon oxide tetrahedrons with an aluminum oxide octahedron (Fig.…”
Section: Nanocomposites Based On Thermoplastic Starch and Nanoclaysmentioning
confidence: 99%
“…The Fig. 7 Scheme of the structure of montmorillonite Nanoclays commonly used in polymer Nanocomposites are montmorillonite and bentonite [68]. They consist on two layer aluminosilicates 2:1 type, and its unit cell is formed by two silicon oxide tetrahedrons with an aluminum oxide octahedron (Fig.…”
Section: Nanocomposites Based On Thermoplastic Starch and Nanoclaysmentioning
confidence: 99%
“…Polycaprolactone (PCL) is a well‐known biodegradable, semicrystalline synthetic polymer, with good processability and large deformations, but weak tensile mechanical properties and creep resistance 3–8 . Many researchers have shown that the competitiveness of PCL can be enhanced with the addition of small amounts of nanofillers 9 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Polycaprolactone (PCL) is a well-known biodegradable, semicrystalline synthetic polymer, with good processability and large deformations, but weak tensile mechanical properties and creep resistance. [3][4][5][6][7][8] Many researchers have shown that the competitiveness of PCL can be enhanced with the addition of small amounts of nanofillers. 9 Clays are natural nanoscale materials which provide new possibilities in improving the properties of polymeric materials due to their small size, high aspect ratio, and excellent mechanical, and thermal properties.…”
Section: Introductionmentioning
confidence: 99%